Pesugihan as a Cultural Belief System in Contemporary Indonesian Drama - Afrianti, Putry; Matugu, Beth N; Kiyan, Ali Daneshvar; Firuza, Toreba; Milad, Abdurahman Ahmed Ali (Journal of Language, Literature, and Educational Research, 2026)
Purpose of the study: This study aims to examine the cultural representation of pesugihan in the drama script Pesugihan Nayan Tula by Afrion using a literary anthropology approach to reveal embedded cultural values, belief systems, and socio-cultural structures reflected in the narrative Methodology: This study employed a qualitative descriptive method using a literary anthropology approach. The primary data source was the 2016 published drama script by Laboratorium Sastra Medan. Data were collected through documentation techniques and analyzed using cultural category frameworks based on Koentjaraningrat’s anthropological theory and Ratna’s literary anthropology perspective. Main Findings: The findings reveal that pesugihan is represented as a cultural belief system rooted in animism, ritual practices, myth, and social structure. The script portrays traditional systems including religious beliefs, ritual offerings, supernatural agreements, and socio-cultural conflicts reflecting moral deviation and community value transformation. Novelty/Originality of this study: This study offers a focused literary anthropology analysis on pesugihan within modern Indonesian drama, integrating classical anthropological theory with contemporary literary text analysis. It advances cultural-literary studies by contextualizing mystical economic practices as structured cultural phenomena within dramatic narrative discourse.